COMPETENCIES THAT ALLOW YOU TO RATIONALLY ORGANIZE A FAMILY HOUSEHOLD - Нурматова Мафтуна Илхамовна (Galaxy International Interdisciplinary Research Journal, 2023)
Family farming is a complex mechanism. Therefore, its management requires parents, and even more so from each family member, to have economic competencies. The age peculiarity allows students to get married and start a family. This circumstance makes them responsible for the formation of the family economy and its effective management. Accordingly, it is important that students have competencies in family farming. The article discusses the competencies important for the rational organization of the family economy.